The structure and intent of Psalm 118 - Potgieter, J. H. (Old Testament Essays, 2003)
In this paper, Psalm 118 is analysed on a stichometric and poetic level. Its division into verse lines, strophes, and stanzas is discussed. It seems that repetition of certain phrases and especially the poetic technique of inclusion are used to delineate strophes and stanzas. By this technique, the poem is not only embellished, but its poetic structure is demarcated and its main ideas are emphasised.
free